Assessing Mediating Role of Financial Satisfaction in the Relationship of Financial Literacy With Quality of Life in Retired Older Adults - Mahsa Kiaei; Fatemeh Mohammadi; Zahra Hosseinkhani; Seyedeh Ameneh Motalebi (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives The world's population is rapidly aging; hence, paying attention to the quality of life (QoL) of the elderly is of great importance. Financial satisfaction is one of the important components of QoL. The present study aims to determine the association between financial literacy and QoL among retired older adults mediated by their financial satisfaction. Methods & Materials This descriptive and cross-sectional study was conducted in 2020 on 270 retired older adults in Qazvin, Iran. The samples were selected through stratified random sampling method from 8 retirement centers in Qazvin, Iran. The data were collected using demographic checklist, the control, autonomy, self-realization, and pleasure (CASP) scale, financial literacy scale, and financial satisfaction scale. Structural equation modeling was used to determine the mediating role of financial satisfaction in the relationship of financial literacy with the QoL. Results The mean age of older adults was 65.17±4.57 years. The majority of them were male (n=166, 61.85%) and married (n=245, 90.7%). Their Mean score of financial literacy and financial satisfaction were 51.60 and 35.11 out of 100, respectively. Their quality of life was at a moderate level (Mean= 63.89 out of 100). The results of the regression analysis showed the significant association of financial literacy (P=0.006, β=-0.17) and financial satisfaction (β=0.25, P<0.001) with the quality of life. The results also confirmed the mediating role of financial satisfaction (P=0.014). Conclusion Financial literacy of the elderly has a significant and positive association with their quality of life mediated by financial satisfaction. Therefore, policymakers in Iran are recommended to develop pre-retirement financial education programs for improving the financial literacy of the elderly.